2022
DOI: 10.1155/2022/2066133
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Suicide among Cancer Survivors Who Developed a Second Malignant Neoplasm

Abstract: Background. Cancer diagnosis entails substantial psychological distress and is associated with dramatically increased risks of suicidal behaviors. However, little is known about the suicide risk among cancer survivors who developed a second malignant neoplasm (SMN). Methods. Using the Surveillance, Epidemiology, and End Results database, we conducted a population-based cohort study involving 7,824,709 patients with first malignant neoplasm (FMN). We measured the hazard ratios (HRs) of suicide death after recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Previous related studies differ in part from our study. Yang et al reported a higher risk of suicide among patients with SPC compared with patients with FPC (Yang et al, 2022). This disparity could be attributed to the inconsistency in the year of diagnosis within their sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous related studies differ in part from our study. Yang et al reported a higher risk of suicide among patients with SPC compared with patients with FPC (Yang et al, 2022). This disparity could be attributed to the inconsistency in the year of diagnosis within their sample.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies among patients with cancer have mainly focused on the suicide death of patients with FPC or a single cancer (Dalela et al, 2016;Kam et al, 2015;Zaorsky et al, 2019), and suicide death has not been assessed in a large sample of patients with SPC. SPC may be a stronger stressor, leading to an increase in suicide death (Yang et al, 2022), or it may account for a decrease in suicide death because of the stronger psychological power acquired from surviving an FPC (Brinkman et al, 2018). As a result, relevant studies concerning suicide death among patients with SPC are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation